Criminal Existence of Additional Compensation Money in Recovering State Financial Losses - Nadhilah Hakim; Mas Anienda Tien (JOSAR (Journal of Students Academic Research), 2022)
Corruption can endanger the country's economy, which not only causes losses to the state, but also causes losses to legal entities on a small or large scale. Corruption has a very close relationship with state financial losses, where state finances contain state rights and obligations that can be worth money. In an effort to recover state financial losses, there are regulations regarding additional penalties in the form of replacement money. The imposition of replacement money is proportional to the amount of assets that have been enjoyed from the proceeds of criminal acts of corruption. The additional penalty of substitute money as an instrument of criminal law is expected to restore wealth that should be owned by the state. This study uses a normative juridical method by using a literature study. The results of this study indicate that even though the reimbursement of money has been given, the return of state financial losses cannot be achieved. This is evidenced by the fact that there are convicts who prefer to carry out substitute prisons rather than paying replacement money. This shows that the additional punishment for substitute money is only a formality and has no essence in recovering state financial losses. Thus, it is necessary to have a statutory regulation that specifically regulates additional criminal compensation so that the convict has no other choice but to pay compensation